Tariff rate quotas: Does administration matter? - Christina Mönnich (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2003)
At the Uruguay Round, tariff rate quotas (TRQs) were intended to serve two purposes: first, to prevent that tariffication would lead – at least on the short term – to a deterioration of market access and second, to create new, minimum market access. The since then observed fill rates do not match with these intentions, being often rather low. A wide-held suspicion explains this with tariff quota administration imposing an extra barrier to trade. It is the aim of this paper to test whether different administrative methods do indeed contribute to explain variation in fill rates and if so, how. A censored regression model for panel data was developed and applied to the EU's TRQs for the years 1995–2000. The data supported the presumption that administration matters, sometimes in surprising ways.
Keywords: 330; Außenhandelskontingent; Agrarzoll; Finanzverwaltung; Zollpolitik; Agrarprotektionismus; Schätzung; EU-Staaten